1,25-dihydroxyvitamin D3 inhibits corneal wound healing in an ex-vivo mouse model - Sel, Saadettin; Trau, Stefanie; Paulsen, Friedrich; Kalinski, Thomas; Stangl, Gabriele I.; Naß, Norbert (Graefe's archive for clinical and experimental ophthalmology, 2016)
Impaired healing of corneal injuries can result in ulceration and complete loss of vision, especially in the elderly. Such patients frequently also exhibit vitamin D insufficiency. 1,25-dihydroxyvitamin D3 is the active vitamin D metabolite. As it affects cell proliferation and inflammation, we herein aimed at elucidating its influence on corneal wound healing after alkali burn by using in vitro and ex vivo techniques.